Sigilo - múltiplas dimensões: ação dos agentes, formas de entendimento e dinâmica organizacional - Busnelo, Homero Cremm (2018)
The study of the secrecy of information in organizations involves the understanding of agents actions and the existence of an institutional support of processes with direct or indirect reflexes in the business of organizations. This work is a multiple case study with application of a survey questionnaire that analyzed three large multinational companies present in Brazil. The main objective of the study was to bring the surface of the actors' visions about the secrecy of information in three hierarchical levels: top executive, manager and supervision. The study also compares these visions at the same levels between the organizations surveyed and in the interrelations with institutions, with the market and under the influence of the nexus of contracts and their objective and subjective boundaries. The existing theoretical basis on secrecy is fragmented in different areas such as sociological, economic, legal, management and even historical. This study proposes a circle of interactions that exist in the treatment of secrecy in different social spaces such as private or public organizations, military, secret societies and academics. The visions of the studied actors are broad in the micro environments of their organizations and some participation in the macro environment when external contacts occur and their risks, impacts and consequences. In the end, the study concludes on the visions found in the different areas where secrecy is treated as an important asset and forms of disclosure when applicable or in the existence or absence of mitigation actions in case of leaks.